A prática da formação de uma cultura acadêmica empreendedora: aprendizados acumulados a partir da experiência de um Instituto Nacional de Ciência e Tecnologia - Priscila Maria Teixeira Gonçalves de Souza (2019)
INCTs (National Institutes of Science and Technology) are currently considered the most important national network research projects in strategic areas with large amounts of public resources. Despite the relevant knowledge generation and human resources training, these INCTs have resulted in very limited technological innovation. In this study, a restructuring of INCT Midas was carried out in order to effectively incorporate elements of innovation and entrepreneurship. From the different planned actions, two programs are presented here: the Midas Business Laboratory (LNM) and the Technological Entrepreneurship Events (short courses and workshops), which were applied in different research institutions in Brazil. The LNM was a pre-acceleration program for environmental technologies, carried out in partnership with Biominas Brazil, whose target audience were students and professors related to the INCT Midas. In the LNM program 42 technologies in the areas of new materials, contaminants removal, glycerin treatment, new processes, waste assessment and biomass utilization participated in the initial stage. 10 technologies were selected and joined the program during three months of face-to-face and remote stages, using different business tools to create academic spin-offs or licensing. The Events of Technological Entrepreneurship were structured according to the most modern programs of entrepreneurship education, adjusting contents for times of 4-12 h and were offered in the following institutions and events UFMG, 69th SBPC (UFMG), 19th CBCat (UFOP), XXXI ERSBQ (UNIFEI), UFRN, Cidade Empreendedora (UFRN), UFSC, 41st Annual Meeting of the SBQ (Foz do Iguaçu), Chemist Week (UFU). This study shares the structures and operation of these programs, their executions and main learnings aiming at the possibility of replication in other INCTs. Some of the impacts observed from these programs were: tool / content development, definition of the modus operandi for a preacceleration non-presential program, content development, entrepreneurial culture promotion, development of interpersonal skills of academic participants, teacher and students connections to the entrepreneurial ecosystem stakeholders generating opportunities to create academic and TT spin-offs.